Stability, flexural behavior and compressive strength of ultra-lightweight fiber-reinforced foamed concrete with dry density lower than 100 kg/m3. (1st July 2022) - Falliano, Devid; Parmigiani, Silvia; Suarez-Riera, Daniel; Ferro, Giuseppe Andrea; Restuccia, Luciana
Abstract: Ultra-lightweight (<100 kg/m 3 ) foamed concrete based on Portland cement was produced by means of preformed foam. The effect of two different protein foaming agents and the addition of polypropylene microfibers on both the fresh and the hardened properties was investigated. In particular, slump, stability, flexural strength, compressive strength, porosity, pore sizes, and distribution were evaluated. The study revealed that the addition of microfibers (5% by mass of cement) gives rise to a three-dimensional system of connection that positively affects stability and mechanical performance. The addition of microfibers gives rise to an increase in flexural strength and compressive strength of approximately 300% and 22% respectively, promoting a ductile behavior, while not compromising workability. Furthermore, the use of a surfactant with higher foaming properties positively affects microstructural pore characteristics, thus enhancing workability and compressive strength. Flexural strength and compressive strength at 28 days of the investigated ultra-lightweight fiber-reinforced foamed concrete are, on average, 0.027 MPa and 0.22 MPa, respectively. Highlights: Stable ultralightweight foamed concrete ULFC with dry density lower than 100 kg/m3. ULFC and F-ULFC (with fibers) exhibit an elastic-plastic compression behavior. The presence of fibers gives rise to a ductile flexural behavior. More consistent ULFCs are characterized by bubbles of smaller size. More consistent ULFCs have higher compressive strength.